2018
DOI: 10.1016/j.talanta.2017.12.042
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-based materials modified with magnetite nanoparticles for enrichment of phospholipids

Abstract: A polymeric material modified with magnetic nanoparticles (MNPs) has been synthesized and evaluated as sorbent both for solid-phase extraction (SPE) and dispersive magnetic solid-phase extraction (MSPE) of phospholipids (PLs) in human milk samples. The synthesized sorbent was characterized by scanning electron microscopy and its iron content was also determined. Several experimental variables that affect the extraction performance (e.g. loading solvent, breakthrough volume and loading capacity) were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Polymer-based nanoparticles (NPs) are highly biocompatible and are commonly used as tools to facilitate drug delivery, having received approval from the US Food and Drug Administration for medical use. [23][24][25][26] NPs have previously been demonstrated to significantly enhance solubility, bioavailability, efficacy, and pharmacokinetic profiles of encapsulated drugs. 27,28 These NPs are also highly multifunctional, less toxic, and less immunogenic as compared to many other drug delivery nanoplatforms.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer-based nanoparticles (NPs) are highly biocompatible and are commonly used as tools to facilitate drug delivery, having received approval from the US Food and Drug Administration for medical use. [23][24][25][26] NPs have previously been demonstrated to significantly enhance solubility, bioavailability, efficacy, and pharmacokinetic profiles of encapsulated drugs. 27,28 These NPs are also highly multifunctional, less toxic, and less immunogenic as compared to many other drug delivery nanoplatforms.…”
Section: Introductionmentioning
confidence: 99%
“…The first strategy (procedure A) was adapted from a previous work [25]. Thus, the GMA-based monolith in ETFE tubing was modified by pumping through a solution of APTMS in acetone at 60°C (column oven) at 0.05 mL min -1 using an HPLC pump for 2 h. Upon completion of the reaction, the column was washed with ethanol and dried.…”
Section: Immobilization Of Mnps Onto Polymeric Monoliths In Etfe Tubingmentioning
confidence: 99%
“…Polymer Nanoparticles (NPs) are extensively used drug delivery matrix material with good biocompatibility, which have been approved by the US Food and Drug Administration [23,24]. Previous work reported that NPs can improve the efficacy, solubility, bioavailability and pharmacokinetic profiles of drugs [25,26].…”
Section: Introductionmentioning
confidence: 99%